2011
DOI: 10.1002/cphc.201100167
|View full text |Cite
|
Sign up to set email alerts
|

Correlated Absorption and Photoluminescence of Single Gold Nanoparticles

Abstract: We perform simultaneous absorption (photothermal) and fluorescence detection of gold nanospheres with diameters of 80, 60, 40, 20, 10, and 5 nm. We unambiguously identify the same individual nanoparticles (NPs) over large areas (>400 μm(2)) by means of atomic force microscopy (AFM) and optical absorption (photothermal) microscopy. We correlate the height of NPs measured with AFM with absorption and fluorescence signals from the same individual NPs. That allows us to compare their brightness and estimate their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
61
1
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(67 citation statements)
references
References 40 publications
(56 reference statements)
4
61
1
1
Order By: Relevance
“…Our measurements showed that, for holes with a diameter from 20 nm to 1 µm, the photoluminescence efficiency is almost the same and is about 10 −6 , which is approximately 10 4 times higher compared to the photoluminescence from the surface of the bare gold. These data agree well with measurement results for spherical gold nanoparticles [6,17]. The fact supports plasmonic nature of the measured high efficiency of the PL process in nanoholes.…”
Section: Photoluminescence Of Individual Nanoholesupporting
confidence: 91%
“…Our measurements showed that, for holes with a diameter from 20 nm to 1 µm, the photoluminescence efficiency is almost the same and is about 10 −6 , which is approximately 10 4 times higher compared to the photoluminescence from the surface of the bare gold. These data agree well with measurement results for spherical gold nanoparticles [6,17]. The fact supports plasmonic nature of the measured high efficiency of the PL process in nanoholes.…”
Section: Photoluminescence Of Individual Nanoholesupporting
confidence: 91%
“…The particles and the glass substrates were cleaned from organic ligands by repeated flushing and ozone cleaning. We checked that all particles used in the present work were isolated single ones, by photothermal contrast [24]. The particles were covered with the liquid (water or n-pentane), so that bubbles could form in the half-space limited by the flat glass-liquid interface.…”
Section: Methodsmentioning
confidence: 99%
“…[ 29,33 ] In contrast, the polarization modulation depth for metal nanoparticles, much larger in size than the few atom silver clusters addressed in this paper, varies widely with a strong dependence on the specifi c nanoparticle shape. [ 31 ] Because the fl uorescence quantum yields of metal nanoparticles are very small (∼0.001% or less), [ 9,34 ] most polarization measurements have focused on determining the single nanoparticle extinction as a function of the polarization, θ ex , of the excitation light, using techniques such as photothermal imaging, [ 35 ] light scattering microscopy, [ 36 ] and extinction microscopy. [ 37 ] The intensity dependence on θ ex has the same overall sinusoidal form as for individual molecules Equation 2 .…”
Section: Full Paper Full Paper Full Papermentioning
confidence: 99%
“…[ 6 ] Such silver "nanoclusters", with just tens of metal atoms, are in a different size regime from metal nanoparticles of several to tens of nanometers dimensions that are the focus of current nanoplasmonics research. [7][8][9] Thus, beyond their current uses as biolabels and sensors, metal nanoclusters that are stabilized by such a versatile ligand as DNA, which itself can assemble into elaborate nanoscale shapes, [ 10 ] have the potential to realize metal-organic dipole, transitions into a dark state (reversible and irreversible photobleaching) and spectral jumps. [ 29 ] Another example of the strength of polarization resolved measurements is the study of Au 25 nanoclusters stabilized by bovine serum albumin (BSA).…”
Section: Introductionmentioning
confidence: 99%